Optimum build orientation OF3D printed parts for a robot gripper - Altaf, K. (Asian Research Publishing Network, 2017)
Build orientation is one of chief factors which could affect the build time and support material requirement in fused deposition modelling (FDM)3D printing (3DP) process. Intelligent building orientation is inevitable for prototyping of parts, corresponding to least build time and support material. Decision of build orientation could be simple for standard and uniform parts; nevertheless, same practices could not be applied for prototyping of tailored parts. Prototyping of intricate, non-standard and customized parts usually demand pre-processing, prior to go for FDM printing to identify optimum build orientation, such that build time and material requirement could be mitigated. The present study investigates the best possible build orientation to attenuate build time and support material, while prototyping an intricate and complex robot arm. The standard practices for build orientation of couture parts of the robot arm assembly under study do not exist. Therefore effort has been made to devise build orientation to develop the parts rapidly and economically. © 2006-2017 Asian Research Publishing Network (ARPN).